Grounded theory - Oktay, Julianne S. (Oxford : Oxford University Press, 2012)
With practice exercises, guidelines for formulating problems and gathering and analyzing data, tips for working with software this pocket guide offers social work researchers a strong practical introduction to grounded theory research.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Grounded theory